Image quality assessment based on the perceived structural similarity index of an image - Juncai Yao; Jing Shen; Congying Yao (Mathematical Biosciences and Engineering, 2023)
Image quality assessment (IQA) has a very important role and wide applications in image acquisition, storage, transmission and processing. In designing IQA models, human visual system (HVS) characteristics introduced play an important role in improving their performances. In this paper, combining image distortion characteristics with HVS characteristics, based on the structure similarity index (SSIM) model, a novel IQA model based on the perceived structure similarity index (PSIM) of image is proposed. In the method, first, a perception model for HVS perceiving real images is proposed, combining the contrast sensitivity, frequency sensitivity, luminance nonlinearity and masking characteristics of HVS; then, in order to simulate HVS perceiving real image, the real images are processed with the proposed perception model, to eliminate their visual redundancy, thus, the perceived images are obtained; finally, based on the idea and modeling method of SSIM, combining with the features of perceived image, a novel IQA model, namely PSIM, is proposed. Further, in order to illustrate the performance of PSIM, 5335 distorted images with 41 distortion types in four image databases (TID2013, CSIQ, LIVE and CID) are used to simulate from three aspects: overall IQA of each database, IQA for each distortion type of images, and IQA for special distortion types of images. Further, according to the comprehensive benefit of precision, generalization performance and complexity, their IQA results are compared with those of 12 existing IQA models. The experimental results show that the accuracy (PLCC) of PSIM is 9.91% higher than that of SSIM in four databases, on average; and its performance is better than that of 12 existing IQA models. Synthesizing experimental results and theoretical analysis, it is showed that the proposed PSIM model is an effective and excellent IQA model.